Genetic Diversity 20 Bean Varieties using Microsatellite Technique (SSR) - Nguyen, Phuoc Trong; Minh Le, Khang; Chi, Hieu Bui; Nguyen, Loan Hong Thi; Nguyen, Lang thi (International Journal of Environment, Agriculture and Biotechnology, 2023)
Agro-morphological characters and PCR based markers have provided valuable information about genetic diversity of bean collection in HATRI . Analysis on SSR molecular markers: out of a total of 44 primers conducted genetic diversity studies, only 28 primers amplified the product on 20 bean varieties. Through the SSR marker data with 28 primers used, 20 varieties are classified into 4 main groups. In the subgroup of the SSR on 28 molecular markers are noted with 4 distinct groups. Molecular markers to be able to indirectly assess the presence or absence of selected genes thanks to markers without environmental influences. The diversity index analyzes according to the high SSR method (H = 0.384) while the diversity index of stick beans. The results presented here are the first steps towards a better understanding of varieties introduced from countries and may help guide future research into the crop.